Benefits and Potential Harms of Human Immunodeficiency Virus Self-Testing Among Men Who Have Sex With Men in China: An Implementation Perspective. Issue 4 (April 2017) - Qin, Yilu; Tang, Weiming; Nowacki, Amy; Mollan, Katie; Reifeis, Sarah A.; Hudgens, Michael G.; Wong, Ngai-Sze; Li, Haochu; Tucker, Joseph D.; Wei, Chongyi
Abstract : Background: Human immunodeficiency virus self-testing (HIVST) holds great promise for reaching high-risk key populations who do not access facility-based services. We sought to characterize unsupervised HIVST implementation among men who have sex with men in China. Methods: We conducted a nationwide online survey in China. Eligible men were at least 16 years, had anal sex with a man, and had recent condomless sex. We assessed benefits (first-time testing, increased testing frequency, confirmatory testing) and potential harms (coercion, violence, suicidality) of HIVST. Among men who have sex with men who reported ever testing for human immunodeficiency virus (HIV), we identified correlates of HIVST as first-time HIV test being a self-test using multivariable logistic regression. Results: Among 1610 men who met the eligibility criteria and started the survey, 1189 (74%) completed it. Three hundred forty-one (29%) of 1189 reported ever self-testing for HIV. Human immunodeficiency virus prevalence was 7% (24/341) among self-testers and 5% (15/306) among non–self-testers. Two hundred (59%) of 341 men who self-tested reported HIVST as a first-time HIV test. Thirty-one (9%) men experienced coercion with HIVST. Thirty-one (78%) of 40 men with positive HIV self-tests sought confirmation. Multivariable analysis revealed that HIVST as first-time HIV test was associated with younger age (odds ratio [OR], 0.95; 95% confidence interval [CI], 0.92–0.99), not being "out" (OR, 2.28; 95% CI, 1.60–3.28), not using the internet to meet sex partners (OR, 0.39; 95% CI, 0.22–0.69), and group sex (OR, 1.74; 95% CI, 1.02–2.9). Conclusions: Human immunodeficiency virus self-testing reached high-risk individuals that had never received facility-based testing. Further implementation research is needed to better understand HIVST outside of research programs. Abstract : A study of men who have sex with men in China found that human immunodeficiency virus self-testing is common and reaches individuals that have not previously tested.